Low-impedance zwitterionic conductive polymer and preparation method thereof
By introducing zwitterionic groups into polyethylene dioxythiophene and polypropylene dioxythiophene polymers and using palladium catalyzed direct arylation polymerization method, the problem of high impedance and non-specific protein adsorption in bioelectronic devices is solved, and low Impedance and anti-adhesion conductive polymer materials are suitable for the field of bioelectronic materials.
Patent Information
- Application Number
- CN202311008119.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-08-10
AI Technical Summary
In the prior art, polyethylene dioxythiophene and polypropylene dioxythiophene polymer materials have high impedance and nonspecific protein adsorption problems in bioelectronic devices, resulting in increased signal noise and chronic immune response.
By introducing zwitterionic groups into the polymer, the palladium catalytic direct arylation polymerization method is used to synthesize low-impedance zwitterionic conductive polymers in one step, improving the material's anti-adhesion ability and electrochemical properties.
It realizes the low electrochemical impedance and non-specific adhesion resistance of conductive polymers, and is suitable for the field of bioelectronic materials, reducing the risk of signal noise and immune response.
Smart Images

Figure CN119463128A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a low-impedance zwitterionic conductive polymer and a preparation method thereof. Background Art
[0002] Polyethylene dioxythiophene and polypropylene dioxythiophene polymer materials are widely studied as a new generation of implantable and wearable electronic materials due to their mechanical flexibility, high conductivity and biocompatibility. Polyethylene dioxythiophene and polypropylene dioxythiophene polymer materials have the characteristics of mixed ion-electron conductivity and high capacitance as implantable bioelectrode materials. The mechanical flexibility and high conductivity of biomaterial conductive polymers correspond to the high molecular weight of the polymer. However, unmodified polymers cannot solve the problem of nonspecific protein adsorption, which will lead to increased interfacial impedance and even chronic immune response, causing glial scar tissue to form around electronic devices. Inactive scar tissue will reduce or even eliminate the stimulation signal.
[0003] In addition, the impedance of the surface coating material is also critical. The study on the frequency dependence of electrode / electrolyte impedance in the literature 1 (Proceedings of SPIE, 2016, 9944, 994404) shows that the signal transmission between the bioelectrode and tissue interface is not only related to the difference in interface capacitance, but also significantly related to the difference in interface resistance. Low resistance can minimize the noise of the signal and can be used to reduce the inherent noise floor of the system. Therefore, it is crucial to reduce the impedance of the conductive polymer.
[0004] At present, the synthesis of poly 3,4-propylene dioxythiophene is usually based on electrochemical polymerization, oxidative polymerization and transition metal catalyzed polymerization. Document 2 (J. Mater. Chem. B, 2021, 9, 2717) points out that for polypropylene dioxythiophene derivatives prepared by electrochemical polymerization, their development is limited by low yield, low molecular weight, poor polymer regularity, and inability to be prepared on a large scale. At the same time, the complex reaction conditions of oxidative polymerization may break the bridging group connecting the side group, causing the conductive polymer to lose its ability to resist nonspecific adhesion and lead to the emergence of chronic immune response. Document 3 (Chemistry of materials, 2022, 34, 2752-2763) Chemical bond breakage occurred in the oxidative polymerization using ferric chloride as an oxidant. Transition metal catalyzed polymerization usually has mild reaction conditions, and the connected chemical bonds have excellent tolerance in the reaction. Among them, the direct arylation polymerization method extended by this method has the advantages of simple reaction, green environmental protection and atom economy, and can be used as a potential means for preparing conductive polymers containing zwitterionic groups.
[0005] Therefore, the present invention will prepare a highly anti-fouling and conductive polymer material with extremely low electrochemical impedance, and will also develop a high-efficiency and high-quality synthesis method thereof. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention provides a low-impedance zwitterionic conductive polymer and a preparation method thereof;
[0007] To achieve the above object, the scheme adopted by the present invention is as follows:
[0008] A low-impedance zwitterionic conductive polymer, the repeating unit of which contains two independent zwitterionic groups.
[0009] The low-impedance zwitterionic conductive polymer as described above has an electrochemical impedance significantly lower than that of a conductive polymer without zwitterionic groups and a conductive polymer with only one zwitterionic group in a repeating unit.
[0010] The ability of the low-impedance zwitterionic conductive polymer as described above to resist the adhesion of biological molecules, viruses, cells, bacteria and fungi is significantly better than that of the conductive polymer having only one zwitterionic group in the repeating unit.
[0011] As described above, a low-impedance zwitterionic conductive polymer having a general structural formula The electrochemical impedance of the polymer is significantly lower than that of the polymer without zwitterions. and one repeating unit containing only one zwitterionic group Wherein, R1 and R2 are zwitterionic groups independent of each other, and n is a natural number greater than 20.
[0012] A low impedance zwitterionic conductive polymer as described above, the zwitterionic conductive polymer contains a zwitterionic group functional monomer Where R1 and R2 are Any one of the independent ones, where Y is Any one of the following, x, y are integers, and 0≤x≤20, 0≤y≤20.
[0013] As the preferred technical solution:
[0014] The method for preparing a low-impedance zwitterionic conductive polymer as described above comprises the step of synthesizing an anti-nonspecific adhesion polymer by direct arylation polymerization of an aromatic hydrocarbon to be activated in the presence of a palladium catalyst, an oxidant, a solvent and a nitrogen-containing heterocyclic ligand; the aromatic hydrocarbon to be activated is a functionalized monomer containing a double-chain zwitterionic functional group.
[0015] In the method for preparing a low-impedance zwitterionic conductive polymer as described above, the molar ratio of the aromatic hydrocarbon to be activated, the halogenated aromatic hydrocarbon, the palladium catalyst, the nitrogen-containing heterocyclic ligand and the oxidant is 1:1:0.01-0.2:0.02-0.5:1-10, and the ratio of the volume of the solvent to the molar number of the halogenated aromatic hydrocarbon is 0.001-1 L / mol.
[0016] The method for preparing a low-impedance zwitterionic conductive polymer as described above is carried out under an inert atmosphere, the reaction temperature is 60-140° C., the reaction time is 1-120 h, and more preferably 100-160° C., and the reaction time is 1-36 h.
[0017] The method for preparing a low-impedance zwitterionic conductive polymer as described above, wherein the nitrogen-containing heterocyclic ligand is Wherein, R3 to R7 are each independently selected from a hydrogen atom, an alkyl group, an alkoxy group, a fluorine atom, a chlorine atom, a cyano group, a nitro group, a dimethylamino group and a trifluoromethyl group.
[0018] In the method for preparing a low-impedance zwitterionic conductive polymer as described above, the palladium catalyst is palladium acetate, palladium pivalate or palladium chloride, the oxidant is copper acetate, copper valerate, copper sulfate or copper chloride, and the solvent is N,N-dimethylformamide or N,N-dimethylacetamide.
[0019] Principle of the invention:
[0020] Generally speaking, for zwitterionic functionalized conductive polymer materials, the introduction of large zwitterionic groups will bring some problems: the introduction of insulating zwitterionic side chains will reduce the overall conductivity of the polymer; the larger side chains will increase the distance between the molecular chains, which is not conducive to charge conduction; the introduction of large side chains will also cause the π-π plane of the conjugated polymer to distort and reduce the charge conduction ability of its molecular chain. However, the experimental results show that the impedance of polypropylene dioxythiophene without zwitterionic side chain functionalization is 14.69Ω / cm 2 The impedance of polypropylene dioxythiophene functionalized with a zwitterionic side chain is 6.39Ω / cm 2 , and the impedance of polypropylene dioxythiophene functionalized with two zwitterionic side chains can be as low as 2.08Ω / cm 2. That is to say, the introduction of zwitterionic groups significantly reduces the electrochemical impedance of polymer materials. It is particularly interesting that when a zwitterionic side chain is introduced into a repeating unit, the impedance of the conductive polymer material is reduced to 43% of that of polypropylene dioxythiophene without zwitterionic groups; and when two zwitterionic side chains are introduced into a repeating unit, the impedance of the conductive polymer material is reduced to 33% of that of polypropylene dioxythiophene functionalized with a zwitterionic side chain. The possible reasons for the above phenomenon are as follows: zwitterionic groups are introduced into conductive polymer materials, and zwitterions can significantly improve the ionic conductivity of conductive polymers. This enhancement mechanism is mainly attributed to the large dipole moment of zwitterions, which is usually 7-8 times larger than that of polar solvents. The large dipole moment gives the material a large dielectric constant, thereby shielding the electrostatic attraction between anions and cations, which is conducive to the dissociation of ions with opposite charges. In addition, zwitterions also provide migration channels for ions under the action of an external electric field, allowing an ion to jump to the next binding site. At the same time, the degree of hydration is also crucial to ion transport in polymer materials. When hydration weakens, ion mobility usually decreases. Since zwitterionic polymers have dense and stable hydration layers and strong water retention, enriching zwitterions in zwitterionic conductive polymers is also beneficial to ion transport. Although the electronic conductivity of zwitterionic functionalized conductive polymers decreases, the significantly improved ionic conductivity can still significantly improve the material impedance.
[0021] The palladium-catalyzed direct arylation mechanism introduced in the present invention is as follows: under the action of a divalent palladium catalyst, a pyridine ligand / acetylglycine ligand is complexed with palladium to form a reaction intermediate, which is first subjected to oxidative addition, and the halogen is removed to form a Pd-C bond, forming a stable intermediate. The polypropylene dioxythiophene derivative polymerization unit approaches the intermediate, and its CH bond undergoes a metal-coordinated deprotonation process, causing the CH bond to break, and the proton is transferred to acetylglycine to form a Pd-C bond; secondly, the second polypropylene dioxythiophene derivative polymerization unit continues to participate in the reaction, undergoes a similar metal-coordinated deprotonation process, and forms a second Pd-C bond; then, a CC bond and zero-valent palladium Pd are formed through reduction elimination. Finally, the divalent copper catalyst has an oxidative effect, oxidizing zero-valent palladium to divalent palladium to complete the cycle, thereby increasing the chain length of the polymer.
[0022] Beneficial Effects
[0023] (1) A low-impedance zwitterionic conductive polymer of the present invention has simple and rapid steps, and the functional groups have good stability during the reaction, and is suitable for industrial production;
[0024] (2) The anti-nonspecific adhesion polymer obtained by the present invention has low impedance, can resist cell adhesion, and has broad application prospects in the field of bioelectronic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The UV-visible spectrum of a low-impedance zwitterionic conductive polymer prepared in Example 1;
[0026] Figure 2 This is a hydrogen nuclear magnetic resonance spectrum of a low-impedance zwitterionic conductive polymer prepared in Example 1.
[0027] Figure 3 This is the electrochemical impedance diagram of a low-impedance zwitterionic conductive polymer prepared in Example 1.
[0028] Figure 4 This is a diagram showing the anti-cell adhesion of a low-impedance zwitterionic conductive polymer prepared in Example 1. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0030] Example 1
[0031] A method for preparing a low-impedance zwitterionic conductive polymer, the specific steps are as follows:
[0032] (1) Preparation of raw materials:
[0033] Palladium catalyst: palladium acetate;
[0034] Oxidant: copper acetate;
[0035] Solvent: N,N-dimethylformamide;
[0036] Nitrogen-containing heterocyclic ligands: pyridine;
[0037] Aromatic hydrocarbons to be activated:
[0038] (2) Under an argon atmosphere, in the presence of a palladium catalyst, an oxidant, a solvent, and a pyridine ligand, the activated aromatic hydrocarbon and the halogenated aromatic hydrocarbon are subjected to a direct arylation polymerization reaction at 120° C. for 12 h to synthesize an anti-nonspecific adhesion polymer in one step;
[0039] The molar ratio of the aromatic hydrocarbon to be activated, the halogenated aromatic hydrocarbon, the palladium catalyst, the pyridine ligand and the oxidant is 1:1:0.1:0.2:2.5, and the ratio of the volume of the solvent to the molar number of the halogenated aromatic hydrocarbon is 0.125 L / mol.
[0040] The structural formula of the obtained anti-nonspecific adhesion polymer is The degree of polymerization is 37; the yield is 86%; the impedance is 4.69Ω; and it has anti-fouling properties.
[0041] like Figure 1 The ultraviolet spectrum shows that the maximum absorption wavelength of the polymer is 478nm.
[0042] like Figure 2 As shown in the H NMR spectrum, H with different chemical shifts in the molecule are marked in the figure.
[0043] Example 2
[0044] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0045] (1) Preparation of raw materials;
[0046] Palladium catalyst: palladium pivalate;
[0047] Nitrogen-containing heterocyclic ligands:
[0048] Oxidant: copper valerate;
[0049] Deprotonated ligand: acetylglycine;
[0050] Solvent: N,N-dimethylformamide;
[0051] Aromatic hydrocarbons to be activated:
[0052] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 160° C. for 6 hours in a nitrogen atmosphere to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.05:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.05 L / mol.
[0053] The structural formula of the obtained polythiophene conjugated polymer is: The degree of polymerization is 45; the yield is 89%; the impedance is 3.5Ω; and it has anti-fouling properties.
[0054] Example 3
[0055] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0056] (1) Preparation of raw materials;
[0057] Palladium catalyst: Palladium pivalate
[0058] Nitrogen-containing heterocyclic ligands:
[0059] Oxidant: copper sulfate;
[0060] Deprotonated ligand: acetylglycine;
[0061] Solvent: N,N-dimethylformamide;
[0062] Aromatic hydrocarbons to be activated:
[0063] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 100° C. for 12 hours under an argon atmosphere to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:10:10, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.1 L / mol.
[0064] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 98%, the degree of polymerization is 55, the impedance is 2.2Ω; it has anti-fouling properties.
[0065] Example 4
[0066] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0067] (1) Preparation of raw materials;
[0068] Palladium catalyst: palladium chloride;
[0069] Nitrogen-containing heterocyclic ligands:
[0070] Oxidant: copper chloride;
[0071] Deprotonated ligand: acetylglycine;
[0072] Solvent: N,N-dimethylacetamide;
[0073] Aromatic hydrocarbons to be activated:
[0074] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, under an argon atmosphere, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 120° C. for 24 hours to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.1:0.2:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 1 L / mol.
[0075] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 100%, the degree of polymerization is 77, the impedance is 3.33Ω, and it has anti-fouling properties.
[0076] Example 5
[0077] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0078] (1) Preparation of raw materials;
[0079] Palladium catalyst: palladium chloride;
[0080] Nitrogen-containing heterocyclic ligands:
[0081] Oxidant: copper chloride;
[0082] Deprotonated ligand: acetylglycine;
[0083] Solvent: N,N-dimethylacetamide;
[0084] Aromatic hydrocarbons to be activated:
[0085] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, under an argon atmosphere, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 140° C. for 36 hours to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.125 L / mol.
[0086] The structural formula of the obtained polythiophene conjugated polymer is: The yield was 91% and the degree of polymerization was 55.
[0087] Example 6
[0088] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0089] (1) Preparation of raw materials;
[0090] Palladium catalyst: palladium acetate;
[0091] Nitrogen-containing heterocyclic ligands:
[0092] Oxidant: copper acetate;
[0093] Deprotonated ligand: potassium pivalate;
[0094] Solvent: N,N-dimethylformamide;
[0095] Aromatic hydrocarbons to be activated:
[0096] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, the activated aromatic hydrocarbon is directly oxidized and arylated in a helium atmosphere at 100°C for 0.2 h to synthesize a polythiophene conductive polymer in one step. Figure 1 As shown; wherein, the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.125 L / mol.
[0097] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 58%, the degree of polymerization is 45, and the impedance is 1.69Ω; it has anti-fouling properties.
[0098] Example 7
[0099] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0100] (1) Preparation of raw materials;
[0101] Palladium catalyst: palladium acetate;
[0102] Nitrogen-containing heterocyclic ligands:
[0103] Oxidant: copper acetate;
[0104] Deprotonated ligand: cesium pivalate;
[0105] Solvent: N,N-dimethylformamide;
[0106] Aromatic hydrocarbons to be activated:
[0107] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 120° C. for 1 h in a helium atmosphere to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.125 L / mol.
[0108] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 71%, the degree of polymerization is 88, the impedance is 3.9Ω, and it has anti-fouling properties.
[0109] Example 8
[0110] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0111] (1) Preparation of raw materials;
[0112] Palladium catalyst: palladium acetate;
[0113] Nitrogen-containing heterocyclic ligands:
[0114] Oxidant: copper acetate;
[0115] Deprotonated ligand: acetylglycine;
[0116] Solvent: N,N-dimethylformamide;
[0117] Aromatic hydrocarbons to be activated:
[0118] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 100° C. for 0.2 h in a helium atmosphere to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.125 L / mol.
[0119] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 45%, the degree of polymerization is 21, the impedance is 1.6Ω, and it has anti-fouling properties.
[0120] Example 9
[0121] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0122] (1) Preparation of raw materials;
[0123] Palladium catalyst: palladium acetate;
[0124] Nitrogen-containing heterocyclic ligands:
[0125] Oxidant: copper acetate;
[0126] Deprotonated ligand: acetylglycine;
[0127] Solvent: N,N-dimethylformamide;
[0128] Aromatic hydrocarbons to be activated:
[0129] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 120° C. for 1 h in a helium atmosphere to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.125 L / mol.
[0130] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 68%, the degree of polymerization is 38, and the impedance is 3.4Ω; it has anti-fouling properties.
[0131] Example 10
[0132] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0133] (1) Preparation of raw materials;
[0134] Palladium catalyst: palladium acetate;
[0135] Nitrogen-containing heterocyclic ligands:
[0136] Oxidant: copper valerate;
[0137] Deprotonated ligand: acetylglycine;
[0138] Solvent: N,N-dimethylacetamide;
[0139] Aromatic hydrocarbons to be activated:
[0140] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 140° C. for 3 h in a nitrogen atmosphere to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.125 L / mol.
[0141] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 74%, the degree of polymerization is 49, the impedance is 2.5Ω, and it has anti-fouling properties.
[0142] Embodiment 11
[0143] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0144] (1) Preparation of raw materials;
[0145] Palladium catalyst: palladium chloride;
[0146] Nitrogen-containing heterocyclic ligands:
[0147] Oxidant: copper chloride;
[0148] Deprotonated ligand: acetylglycine;
[0149] Solvent: N,N-dimethylacetamide;
[0150] Aromatic hydrocarbons to be activated:
[0151] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, under an argon atmosphere, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 120° C. for 24 hours to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.125 L / mol.
[0152] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 90%, the degree of polymerization is 98, the impedance is 1.9Ω; it has anti-fouling properties.
[0153] Example 12
[0154] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0155] (1) Preparation of raw materials;
[0156] Palladium catalyst: palladium chloride;
[0157] Nitrogen-containing heterocyclic ligands:
[0158] Oxidant: copper chloride;
[0159] Deprotonated ligand: acetylglycine;
[0160] Solvent: N,N-dimethylacetamide;
[0161] Aromatic hydrocarbons to be activated:
[0162] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, under an argon atmosphere, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 140° C. for 36 hours to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.125 L / mol.
[0163] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 91%, the degree of polymerization is 78, and the impedance is 2.2Ω; it has anti-fouling properties.
[0164] Embodiment 13
[0165] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0166] (1) Preparation of raw materials;
[0167] Palladium catalyst: palladium acetate;
[0168] Nitrogen-containing heterocyclic ligands:
[0169] Oxidant: copper acetate;
[0170] Deprotonated ligand: acetylglycine;
[0171] Solvent: N,N-dimethylformamide;
[0172] Aromatic hydrocarbons to be activated:
[0173] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 100° C. for 12 hours in a helium atmosphere to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.125 L / mol.
[0174] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 91%, the degree of polymerization is 49, the impedance is 2.8Ω, and it has anti-fouling properties.
[0175] Embodiment 14
[0176] A method for preparing a polythiophene conjugated polymer, the specific steps are as follows:
[0177] (1) Preparation of raw materials;
[0178] Palladium catalyst: palladium acetate;
[0179] Nitrogen-containing heterocyclic ligands:
[0180] Oxidant: copper acetate;
[0181] Deprotonated ligand: acetylglycine;
[0182] Solvent: N,N-dimethylformamide;
[0183] Aromatic hydrocarbons to be activated:
[0184] (2) In the presence of a palladium catalyst, a nitrogen-containing heterocyclic ligand, an oxidant, a deprotonated ligand and a solvent, the aromatic hydrocarbon to be activated is subjected to an oxidative direct arylation polymerization reaction at 120° C. for 12 hours in a helium atmosphere to synthesize a polythiophene-based conductive polymer in one step; wherein the molar ratio of the aromatic hydrocarbon to be activated, the palladium catalyst, the nitrogen-containing heterocyclic ligand, the oxidant and the deprotonated ligand is 1:0.01:0.02:2:2, and the ratio of the volume of the solvent to the molar number of the aromatic hydrocarbon to be activated is 0.125 L / mol.
[0185] The structural formula of the obtained polythiophene conjugated polymer is: The yield is 87%, the degree of polymerization is 44, the impedance is 3.1Ω, and it has anti-fouling properties.
Claims
1. A low impedance zwitterionic conductive polymer, characterized in that: Its repeating unit contains two independent zwitterionic groups.
2. A low-impedance zwitterionic conductive polymer according to claim 1, characterized in that: The electrochemical impedance is significantly lower than that of conductive polymers without zwitterionic groups and conductive polymers with only one zwitterionic group in the repeating unit.
3. A low-impedance zwitterionic conductive polymer according to claim 1, characterized in that: Its ability to resist the adhesion of biological molecules, viruses, cells, bacteria and fungi is significantly better than that of conductive polymers containing only one zwitterionic group in the repeating unit.
4. A low-impedance zwitterionic conductive polymer according to claim 2, characterized in that: Zwitterionic conductive polymers have the general structural formula The electrochemical impedance of the polymer is significantly lower than that of the polymer without zwitterions. and one repeating unit containing only one zwitterionic group Wherein, R1 and R2 are zwitterionic groups independent of each other, and n is a natural number greater than 20.
5. A low-impedance zwitterionic conductive polymer according to claim 4, characterized in that: Zwitterionic conductive polymers containing monomers functionalized with zwitterionic groups Where R1 and R2 are Any one of the independent ones, where Y is Any one of the following, x, y are integers, and 0≤x≤20, 0≤y≤20.
6. A method for preparing a low-impedance zwitterionic conductive polymer according to any one of claims 1 to 4, characterized in that: The invention discloses an anti-nonspecific adhesion polymer synthesized in one step by direct arylation polymerization of the aromatic hydrocarbon to be activated in the presence of a palladium catalyst, an oxidant, a solvent and a nitrogen-containing heterocyclic ligand; the aromatic hydrocarbon to be activated is a functionalized monomer containing a double-chain zwitterionic functional group.
7. The method for preparing a low-impedance zwitterionic conductive polymer according to claim 5, characterized in that: The molar ratio of the aromatic hydrocarbon to be activated, the halogenated aromatic hydrocarbon, the palladium catalyst and the oxidant is 1:1:0.01-0.2:0.02-0.5:1-10, and the ratio of the volume of the solvent to the molar number of the halogenated aromatic hydrocarbon is 0.001-1L / mol.
8. The method for preparing a low-impedance zwitterionic conductive polymer according to claim 5, characterized in that: The reaction is carried out under an inert atmosphere, the reaction temperature is 60-140° C., and the reaction time is 1-120 h.
9. The method for preparing a low-impedance zwitterionic conductive polymer according to claim 55, characterized in that: The nitrogen-containing heterocyclic ligand is Wherein, R3 to R7 are each independently selected from a hydrogen atom, an alkyl group, an alkoxy group, a fluorine atom, a chlorine atom, a cyano group, a nitro group, a dimethylamino group and a trifluoromethyl group.
10. A method for preparing a low-impedance zwitterionic conductive polymer according to claim 5, characterized in that: The palladium catalyst is palladium acetate, palladium pivalate or palladium chloride, the oxidant is copper acetate, copper valerate, copper sulfate or copper chloride, and the solvent is N,N-dimethylformamide or N,N-dimethylacetamide.
Citation Information
Patent Citations
Amphiphilic block polymer based on polythiophene, and preparation method and electroactive micelle thereof
CN110818863A
Bionic functionalized PEDOT: PSS film and preparation method thereof
CN111849006A
Nonspecific adhesion resistant conductive polymer and preparation method thereof
CN113416298A